Female butterflies modulate investment in reproduction and flight in response to monsoon‐driven migrations. Issue 2 (18th September 2017) - Bhaumik, Vaishali; Kunte, Krushnamegh
Abstract : Migratory species may display striking phenotypic plasticity during individual lifetimes. This may include differential investment in body parts and functions, differential resource use and allocation, and behavioural changes between migratory and non‐migratory phases. While migration‐related phenotypic changes are well‐reported, their underlying mechanisms are usually poorly understood. Here we compare individuals from migratory (reproductive diapause) and non‐migratory (reproductive) phases of closely related aposematic butterfly species to study how sexual dimorphism and migratory behaviour underlie significant morphological tradeoffs, and propose a plausible scenario to explain the migration‐related phenotypic plasticity observed in females of migratory species. We found that female butterflies invested significantly more in their abdominal mass compared to males irrespective of their migratory phase, and underwent a clear shift in their body mass allocation after the switch from the reproductive diapause phase to the reproductive phase. In reproductive phase, females invested much more in reproductive tissue. This switch occurred as a result of increased abdominal mass (i.e. reproductive tissue mass) without significant reduction in the thoracic mass (i.e. flight muscle mass). Migratory males, however, were not significantly different from non‐migratory males in terms of relative investment in flight and reproductive tissues. These patterns were consistent between migratory and non‐migratory aposematic species within and across clades. While migratory habits may influence the physiology and behaviour of both sexes, long‐distance migration affected female morphology much more markedly compared to that of males. These results show the sex‐specific nature of adaptations to migratory behaviour, and suggest that seemingly disparate life‐history traits such as aposematism and migration may have similar influences on the lifetime energetic investments of insects.